Necessary infrastructure changes for development of FLAVIA corridor - Brožová, Pavlína; Hruška, Roman; Šourek, David (Univerzita Pardubice, 2013)
In Europe, there has been continuous upgrading of rail and water infrastructure. These modernizations are well described in the TEN corridors. However, there isn’t a concept that would ensure the continuity of structures and sections. During solving of the project FLAVIA a report has been completed, in which the development of action plans to eliminate bottlenecks in the transport infrastructure in the Germany - the Black Sea is described. This article presents the most important information concerning this action plan.
Nutná infrastrukturní opatření pro rozvoj koridoru FLAVIA
Notwendige infrastruktur änderungen für entwicklung für FLAVIA corridor